Drivers of Voluntary Intellectual Capital Disclosure in Listed Biotechnology Companies - White, Greg; Lee, Alina; Tower, Gregory (Emerald, 2007)
Purpose: The paper seeks to investigate the key drivers and level of voluntary disclosures in biotechnology company annual reports. Design/methodology/approach: The paper uses an intellectual capital disclosure index score of voluntary disclosures in a large sample of listed biotechnology companies, and tests the relationship between voluntary disclosures of intangible firm value with traditional agency theory variables. The relationships are tested statistically using correlation and multiple-regression analysis. Findings: The key drivers of voluntary intellectual capital disclosures were the level of board independence, firm age, level of leverage and firm size. Multiple regression analysis demonstrated that board independence, leverage and size had a significant relationship with the level of voluntary intellectual capital disclosure. Separate regression controlling for large-sized and small-sized firms demonstrated that voluntary intellectual capital disclosure was only driven by board independence and the levels of firm leverage in large firms. Small firms did not demonstrate this relationship.Research limitations/implications: The implications of this research are that smaller biotechnology companies' managers are not motivated by external debt-holder demands to make voluntary disclosures about intangible firm value. In addition, large biotechnology companies, which are better able to establish independent board oversight, appear more effective at driving voluntary intellectual capital disclosures, perhaps in response to greater demand by owners. A limitation of this study is its Australian context and that data is analysed only from 2005 financial year annual reports. Originality/value: To the authors' knowledge this is an original paper whose findings have valuable implications for managing intellectual capital at the firm level. The paper clearly demonstrates that disclosures about intangible firm value is being driven by traditional agency theory variables and more contemporary corporate governance issues, and that small firms may be ignoring the importance of disclosing more about their intellectual capital.